2012
DOI: 10.1021/ic300172k
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation State of Uranium in A6Cu12U2S15(A = K, Rb, Cs) Compounds

Abstract: Black single crystals of A(6)Cu(12)U(2)S(15) (A = K, Rb, Cs) have been synthesized by the reactive flux method. These isostructural compounds crystallize in the cubic space group Ia ̅3d at room temperature. The structure comprises a three-dimensional framework built from US(6) octahedra and CuS(3) trigonal planar units with A cations residing in the cavities. There are no S-S bonds in the structure. To elucidate the oxidation state of U in these compounds, various physical property measurements and characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 82 publications
0
23
0
Order By: Relevance
“…The salt-like structure comprises isolated US 6 octahedra, MS 4 tetrahedra, and Ba cations. The US 6 octahedra are oriented in the same direction and aligned along the same line along the b and c axes to form pseudo layers 1398.56 (7) 1386.23 (9) r (g cm À3 )…”
Section: Crystal Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The salt-like structure comprises isolated US 6 octahedra, MS 4 tetrahedra, and Ba cations. The US 6 octahedra are oriented in the same direction and aligned along the same line along the b and c axes to form pseudo layers 1398.56 (7) 1386.23 (9) r (g cm À3 )…”
Section: Crystal Structuresmentioning
confidence: 99%
“…Among these compounds, the actinide (An) chalcogenides have also been extensively studied because of the interesting properties of the f orbitals and their potential interaction with d elements in multinary M/AnQ. Among these, we can cite: AMAnQ 3 (A ¼ alkali metal) [6e8], A 6 Cu 12 U 2 S 15 [9], Tl 3 Cu 4 USe 6 [10], KCuThS 3 , K 2 Cu 2 ThS 4 , K 3 Cu 3 Th 2 S 7 [11], K 2 Cu 3 US 5 [12], CsTiUTe 5 [13], Ba 2 Cu 2 AnS 5 [14,15], Ba 9 Ag 10 U 4 S 24 [16], Ba 3 MUS 6 (M ¼ Ba, Fe, Ag) [17], Ba 4 Cr 2 US 9 [18], and Ba 3 Hg 3 U 3 S 18 [19]. These compounds are mainly obtained through solid-state reactions using flux methods [20] or by direct combination of elements.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, U 5 þ chalcogenides are rare and most were obtained serendipitously. However, with the increase in the number of the U 5 þ chalcogenide examples [14][15][16][17][22][23][24], some observations can be made. The use of halide precursors may favor the formation of pentavalent uranium chalcogenides [15].…”
Section: Stabilization Of U 5 þ Chalcogenidesmentioning
confidence: 99%
“…However, a few contain U 3þ , namely U 2 S 3 [11], PdU 2 S 4 [12] , ScUS 3 [12], and ScU 3 S 6 [13] and some contain U 5þ , namely Rb 4 U 4 P 4 Se 26 [14], Tl 3 Cu 4 USe 6 [15], K 2 Cu 3 US 5 [16], and Ba 3 AgUS 6 [17]. Mixed oxidation states have also been reported, namely ScU 8 S 17 [18,19], U x Pd 3 S 4 [20,21] (þ3/þ4), Ba 3.69 US 6 [22] and Ba 8 Hg 3 U 3 S 18 [23] (þ4/þ5), and A 6 Cu 12 U 2 S 15 (A¼K, Rb, Cs) (þ5/þ6) [24].…”
Section: Introductionmentioning
confidence: 95%
“…Although numerous 3d-metal ternary and quaternary uranium chalcogenides have been synthesized [3][4][5][6][7][8][9][10][11] only three compounds have been reported that contain Sc, all of them being ternary sulfides. These are ScU 8 S 17 [12,13], ScUS 3 [14,15], and ScU 3 S 6 [16].…”
Section: Introductionmentioning
confidence: 99%